Venous ulcer review - Paul Bevis; Jonothan Earnshaw (Dove Medical Press, 2011)
Paul Bevis, Jonothan Earnshaw Department of Vascular Surgery, Gloucestershire Royal Hospital, Great Western Road, Gloucester, UKDate of preparation: 3 February 2011Conflict of interest: None declared.Clinical question: What is the best treatment for venous ulcers?Results: Compression aids ulcer healing. Pentoxifylline can aid ulcer healing. Artificial skin grafts are more effective than other skin grafts in helping ulcer healing. Correction of underlying venous incompetence reduces ulcer recurrence.Implementation: Potential pitfalls to avoid are:• Failure to exclude underlying arterial disease before application of compression.• Unusual-looking ulcers or those slow to heal should be biopsied to exclude malignant transformation.Keywords: venous ulceration, ulcer healing